Developing and Validating a Conceptual Change Cognitive Engagement Instrument - Heddy, Benjamin C.; Taasoobshirazi, Gita; Chancey, John B.; Danielson, Robert W. (Frontiers in Education, 2018)
Conceptual change (CC) occurs when learners move from a misconception to a scientifically accepted conception (Heddy et al., 2017). Many researchers agree that deep cognitive engagement is integral to facilitating conceptual change (Sinatra, 2005). Although conceptual change has been explored in great depth, a valid and reliable instrument to assess the type of engagement that occurs during the change process is lacking in the field. In the present study, we designed an instrument meant to assess cognitive engagement during conceptual change. Our measure is modeled after Dole and Sinatra (1998) model theorizing that learners consider message and personal factors when learning new concepts. We used exploratory factor analysis to assess the structure of the Conceptual Change Cognitive Engagement Scale (CCCES) with participants recruited from the M-Turk survey recruitment tool. The CCCES will be beneficial for theoretical understanding related to conceptual change and engagement.